2019
DOI: 10.3390/ijerph16122091
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-Time Sedentary Behavior Is Associated with Psychological Distress and Substance Use among School-Going Adolescents in Five Southeast Asian Countries: A Cross-Sectional Study

Abstract: Sedentary behavior has been found to be associated with poorer mental health. The aim of this study was to estimate associations of sedentary behavior with psychological distress and substance use among adolescents in five Southeast Asian countries. The cross-sectional sample included 32,696 nationally representative samples of school-going adolescents (median age 14 years) from Indonesia, Laos, Philippines, Thailand and Timor-Leste. Leisure-time sedentary behavior, physical activity, psychological distress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 24 publications
7
25
3
Order By: Relevance
“…Another novel discovery from our study is that the levels of recreational sedentary screen-time in males is negatively and significantly associated with levels of alcohol consumption. We found that students who spent more time on recreational screen activities drank less alcohol, which contrasts with others describing a positive association [ 23 ]. A potential explanation may in part follow the displacement hypothesis wherein more attention is given to recreational screen-based activities and less interest (or less time) for social binge drinking.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Another novel discovery from our study is that the levels of recreational sedentary screen-time in males is negatively and significantly associated with levels of alcohol consumption. We found that students who spent more time on recreational screen activities drank less alcohol, which contrasts with others describing a positive association [ 23 ]. A potential explanation may in part follow the displacement hypothesis wherein more attention is given to recreational screen-based activities and less interest (or less time) for social binge drinking.…”
Section: Discussioncontrasting
confidence: 99%
“…Physical activity (PA) had been described to reduce the association between alcohol consumption and risk of death [ 21 ] whereas others had found an association between higher PA and high levels of alcohol consumption [ 22 ]. Another significant lifestyle factor was the amount of recreational sedentary screen-based activities, i.e., internet use and watching television, which was found to be associated with alcohol use [ 23 ]. The relation between high levels of alcohol consumption and recreational sedentary screen-time behaviour remains controversial with reports failing to observe any association between screen-based activities and alcohol [ 24 ], while others have documented a positive association [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of health risk behaviours, high sedentary behaviour, having experienced multiple serious injuries, current tobacco use and ever cannabis use increased the likelihood of having WISD. These findings concur with previous studies [ 8 , 14 , 18 , 19 ]. In a systematic review, Yang et al [ 27 ] showed that prolonged sedentary behaviour was associated with sleep disturbance.…”
Section: Discussionsupporting
confidence: 94%
“…The study showed that being female increased the likelihood of WISD, which was also found in some previous investigations (e.g., [ 19 ]). Generally, girls may be more vulnerable to WISD than boys because of different coping styles in response to stressors [ 13 , 24 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation